The clinical effects of sleep restriction therapy for insomnia: A meta-analysis of randomised controlled trials. (August 2021) - Maurer, Leonie F.; Schneider, Jules; Miller, Christopher B.; Espie, Colin A.; Kyle, Simon D.
Summary: Sleep restriction therapy (SRT) is an established treatment for insomnia that has been used in clinical practise for over 30 y. It is commonly delivered as part of multicomponent cognitive-behavioural therapy (CBT-I) but has also been linked to beneficial effects as a standalone intervention. In order to quantify the efficacy of SRT we performed a comprehensive meta-analysis of randomised controlled trials (RCTs) comparing SRT to minimally active or non-active control groups. Primary outcomes were self-reported insomnia severity and sleep diary metrics at post-treatment. Weighted effect sizes were calculated with Hedges' g and risk of bias was assessed by two independent raters with the Cochrane tool. Our search yielded eight RCTs meeting inclusion/exclusion criteria. Random effects models revealed large treatment effects in favour of SRT versus control for insomnia severity measured with the insomnia severity index ( g = −0.93; 95% CI = −1.15, −0.71), sleep efficiency ( g = 0.91; 95% CI = 0.52, 1.31), sleep onset latency ( g = −0.62; 95% CI = −0.84, −0.40), and wake-time after sleep onset ( g = −0.83; 95% CI = −1.11, −0.55). No effects were found for total sleep time ( g = 0.02; 95% CI = −0.29, 0.34). Results should be interpreted in the context of the small number of comparisons (≤6 per outcome), high risk of bias (6 out of 8 studies met criteria for high risk), and heterogeneity in study design and SRT administration. Only a small number of studies provided outcomes at follow-up (n ≤ 3), hindering assessment of long-term effects. Sleep restriction therapy effectively improves insomnia severity and sleep continuity in the short term; more studies are needed to assess if effects are sustained at long-term follow-up (>3 m). Post-treatment effect sizes appear as large as multicomponent CBT-I. To reduce risk of bias, future studies should consider testing the effects of SRT against control groups that are matched for non-specific treatment effects. Large-scale pragmatic trials are also needed to test if SRT is effective in clinical practise and to quantify effects on daytime functioning and quality of life.